Sleep quality and duration during pandemic uninvolved to impaired fasting glucose and hyperuricemia among health care practitioners - Phebe Hendra; Fenty Fenty; Christianus Heru Setiawan; Leonardo Susanto Utomo; Gregorius Bhaskara Wikanendra; Putu Dyana Christasani; Dita Maria Virginia (Pharmaciana, 2022)
Sleep quality and sleep duration might be more disturbed throughout the pandemic of Covid-19 among health care practitioners (HCPs). It could influence impaired fasting glucose (IFG) and hyperuricemia. Therefore, the objective of this study was to assess the association between sleep with IFG and hyperuricemia among HCPs throughout the pandemic of Covid-19. We conducted a cross-sectional study that enrolled 58 HCPs in the tertiary hospital. Self-reported questionnaire related to their sleep quality and duration using the Pittsburg Sleep Quality Index (PSQI) were performed by participants. Fasting plasma glucose (FPG) and uric acid (UA) were examined after 10-12 hours of fasting to define IFG and hyperuricemia. A total of 58 HCPs detected 34.5% had IFG and 24.1% had hyperuricemia. We could not identify any statistically significant participants characteristic based on IFG. HCPs who shift workers were 21.4% hyperuricemia compared to 54.4 non-hyperuricemia (p=0.03). There were no different characteristics according to the quality and duration of sleep, where 72.4% HCPs had good quality and duration of sleep. However, we found that sleep medication used scores were higher in IFG group (0.30 ± 0.57) than non-IFG (0.03 ± 0.16) (p<0.01). This study could not detect a significant relationship between quality and/or duration of sleep, with IFG and hyperuricemia. Shift worker significant associated with hyperuricemia (p<0.05). The association between quality and duration of sleep with IFG and hyperuricemia was not found among HCPs, especially during the Covid-19 pandemic. An alert where the IFG group had high sleep medication used scores, and shift workers had a lower risk of hyperuricemia.